Turnover Intention and Associated Factors Among Midwives in Jimma, Southwest Ethiopia - Fenta Kebede B; G/Mariam T; Dagnaw Genie Y; Biyazin T; Yetwale Hiwot A (Dove Medical Press, 2023)
Belete Fenta Kebede,1 Tsigereda G/Mariam,2 Yalemtsehay Dagnaw Genie,3 Tsegaw Biyazin,1 Aynalem Yetwale Hiwot1 1School of Midwifery, Jimma University, Jimma, Ethiopia; 2Department of Management, Jimma University, Jimma, Ethiopia; 3Department of Nursing, MizanTepi University, MizanTeferi, EthiopiaCorrespondence: Belete Fenta Kebede, Tel +251932446719, Email belete121wy@gmail.comBackground: Midwife turnover is a major problem and challenge for health-care leaders in Ethiopia. However, to date, little has been documented on turnover intention and its associated factors among midwifery professionals in southwest Ethiopia. Therefore, this study was conducted to fill the information gap on turnover intention and the factors influencing turnover intention among midwives in southwest Ethiopia.Objective: This study aimed to determine the turnover intention and associated factors among midwives, southwest Ethiopia/2022.Methods and Materials: An institutional-based cross-sectional study design was conducted among one hundred twenty one (121) midwives using structured self-administered and a pre-tested questionnaire from May 19/2022-June to 6/2022. Data were entered into Epi-data 4.4.2.1 edited, coded, categorized and entered into the data analysis. Data were analyzed using the statistical package for social science (SPSS) version 24, and the results are presented using figure, tables, and statements. Bivariate and multivariate logistic regression analyses were conducted to determine the factors associated with turnover intention at significance level of 0.25 and 0.05, respectively.Results: In this study, from 121 midwives included in the analysis, approximately 48.76% (95% CI: 39.86- 57.74) of midwives had a turnover intention from their current health-care institution, and 53.72% (95% CI: 44.68- 62.52) of midwives did not have job satisfaction. Being male (AOR: 2.9 (95% CI: 1.14- 7.39)), working in Health center (AOR: 0.20 (95% CI: 0.06- 0.70)) and not having mutual support (AOR: 0.17 (95% CI: 0.07- 0.44)) were associated factors of turnover intention among midwives.Conclusion and Recommendation: In this study, the turnover intention among midwives was higher than that among other local and national figures. Gender, mutual support and type of working institution were factors associated with turnover intention among midwives. Therefore, public health organizations should review their maternity staff to establish teamwork and mutual support.Keywords: associated factors, Jimma, midwives, southwest Ethiopia, turnover intention